PENGEMBANGAN LEARNING MANAGEMENT SYSTEM (E-LEARNING) BERBASIS WORDPRESS DAN LEARNPRESS - Nursanita Nasution; Tatang Raharjo (Akademika, 2023)
Development of Learning Management System (e-Learning) based on Wordpress and Learnpress. This research was conducted to generate and determine the feasibility of web-based e-learning using CMS (Content Management System) WordPress and LearnPress at PT Indo Karya Solusi. This research is a development research with the ADDIE method (Analyze, Design, Develop, Implementation, Evaluation). The steps in this research are the analysis stage, design stage, development stage, implementation stage and evaluation stage. validation of media experts, material experts, one-to-one trials, small group trials and field trials using questionnaires. The data analysis technique for feasibility uses quantitative descriptive analysis. According to the assessment of media experts, this e-learning is feasible to use with a score of 88.8% this is the very good category. According to the material expert's assessment, this e-learning is feasible to use with a score of 93.3% this is the very good category. according to the one-to-one trial, this e-learning is feasible to use with a score of 90.6% this is the very good category. According to the small group trial, this e-learning is feasible to use with a score of 96.13% this is the very good category and according to field trials with a larger number of respondents (50 e-learning training participants), it is feasible to use it with a score of 92,76% this is the very good category. From these tests, it can be concluded that web-based e-learning using CMS (Content Management System) WordPress and LearnPress at PT Indo Karya Solusi is feasible to use.